The Quiet Architecture of Informality: Negotiating Space Through Agency - Rim Mrani; Jérôme Chenal; Hassan Radoine; Hassan Yakubu (Buildings)
Housing informality in Morocco has taken root within Rabat’s formal neighborhoods, quietly reshaping façades, extending plot lines, and redrawing the texture of entire blocks. This ongoing transformation runs up against the rigidity of official planning frameworks, producing tension between state enforcement and tacit tolerance, as residents navigate persistent legal and economic ambiguities. Prior Moroccan studies are neighborhood-specific or socio-economic; the field lacks a city-wide, multi-class analysis linking everyday tactics to long-term governance dilemmas and policy design. The paper, therefore, asks how and why residents and architects across affordable, middle-class, and affluent districts craft unapproved modifications, and what urban order emerges from their cumulative effects. A mixed qualitative design triangulates (i) five resident focus groups and two architect focus groups, (ii) 50 short, structured interviews, and (iii) 500 geo-referenced façade photographs and observational field notes, thematically coded and compared across housing types. In addition to deciphering informality methods and impacts, the results reveal that informal modifications are shaped by both reactive needs—such as accommodating family growth and enhancing security—and proactive drivers, including esthetic expression and real estate value. Despite their legal ambiguity, these modifications are socially normalized and often viewed by residents as value-adding improvements rather than infractions.